2016
DOI: 10.5505/pausbed.2016.96720
|View full text |Cite
|
Sign up to set email alerts
|

Examining Prosptive Teachers’ Attitudes Towards Special Education Lesson in Terms of Some Variables

Abstract: ÖzetBu araştırmanın temel amacı öğretmen adaylarının özel eğitim dersine yönelik tutumlarının bazı değişkenler açısından incelemesidir. Bu amaçla 2014-2015 eğitim-öğretim güz yarıyılında Kafkas Üniversitesi Eğitim Fakültesi Türkçe, Sosyal Bilgiler, Eğitim Bilimleri (PDR) ve Sınıf Öğretmenliği programlarında öğrenim gören 209 öğretmen adayına araştırmacı tarafından geliştirilen "özel eğitim dersine yönelik tutum ölçeği" uygulanmıştır. Özel eğitim dersine yönelik tutum ölçeğinin yapılan geçerlilik çalışmaları so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 10 publications
1
2
0
Order By: Relevance
“…According to the results, no statistically significant difference was found between the participants' sub-dimension scores of the emotional distance towards the other scale according to the age variable. Previous studies (Ten Klooster et al, 2009;Lewis & Stenfert-Kroese, 2010;Yarali, 2015) also support the results obtained from this research. Accordingly, the study reveals that the age variable does not affect emotional distance.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…According to the results, no statistically significant difference was found between the participants' sub-dimension scores of the emotional distance towards the other scale according to the age variable. Previous studies (Ten Klooster et al, 2009;Lewis & Stenfert-Kroese, 2010;Yarali, 2015) also support the results obtained from this research. Accordingly, the study reveals that the age variable does not affect emotional distance.…”
Section: Discussionsupporting
confidence: 90%
“…When the sub-dimension scores of the participants' emotional distance towards the other scale and the gender variable were examined, no statistically significant difference was found. Studies have revealed that the gender variable is not effective on attitudes (Graf et al, 2007;Jerlinder et al, 2010;Fournidou et al, 2011;Colak & Cetin, 2014;Yarali, 2015;Orakci et al, 2016;Ozcan & Ozer, 2018). However, it is also possible to come across studies in the literature with opposite results (Kozub & Lienert, 2003;Meegan & MacPhail, 2006;Ergin, 2007), revealing that there were significant differences in favor of women.…”
Section: Discussionmentioning
confidence: 99%
“…Among the studies examining the attitudes towards individuals with special needs, there are studies pointing at the existence of some positive attitudes (Bek et al, 2009;Yaralı, 2015). A number of works have been done by the state and NGOs to increase society's awareness on individuals with special needs, their adaptation to society and productivity.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Education ensures the formation of an economically, politically, culturally, and socially developed society. The most important and dynamic element of the education system is undoubtedly the teacher (Öztürk, 2005;Karaman, Acar, Kılıç, Buluş, & Erdoğan, 2013;Türk & Çelik, 2013;Akcan & Polat, 2016;Hatipoğlu & Kavas, 2016;Yalçın, 2016).…”
Section: Introductionmentioning
confidence: 99%